A hybrid embedded cohesive element method for predicting matrix cracking in composites. (February 2016) - Joosten, Mathew W.; Dingle, Matthew; Mouritz, Adrian; Khatibi, Akbar A.; Agius, Steven; Wang, Chun H.
Abstract: The complex architecture of many fibre-reinforced composites makes the generation of finite element meshes a labour-intensive process. The embedded element method, which allows the matrix and fibre reinforcement to be meshed separately, offers a computationally efficient approach to reduce the time and cost of meshing. In this paper we present a new approach of introducing cohesive elements into the matrix domain to enable the prediction of matrix cracking using the embedded element method. To validate this approach, experiments were carried out using a modified Double Cantilever Beam with ply drops, with the results being compared with model predictions. Crack deflection was observed at the ply drop region, due to the differences in stiffness, strength and toughness at the bi-material interface. The new modelling technique yields accurate predictions of the failure process in composites, including fracture loads and crack deflection path.